2022
DOI: 10.5582/irdr.2022.01062
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception of inborn errors of metabolism (IEMs) among healthcare students at a selected public university in Klang Valley, Malaysia

Abstract: knowledge, perception, healthcare, inborn errors metabolism Healthcare providers play an important role in improving the health of Inborn Error of Metabolism (IEM) patients. However, IEM knowledge level among local healthcare students has yet to be determined. Thus, the aim of this study is to assess the knowledge and perception of IEM among local healthcare students. An online self-administered questionnaire was distributed to 378 students across the Faculty of Health Science, Pharmacy and Dentistry from a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
2
4
1
Order By: Relevance
“…It is well documented that almost all health sciences students (99.1%) use social media to support learning, which is associated with high academic achievement [ 23 ]. In another study evaluating the level of knowledge about IMD in health sciences students, similar to our findings, the majority of students reported that they used the internet to increase their knowledge about IMD [ 11 ]. It is predicted that implementing a formal curriculum for IMDs through verified and reliable websites or online classes will result in highly effective learning.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…It is well documented that almost all health sciences students (99.1%) use social media to support learning, which is associated with high academic achievement [ 23 ]. In another study evaluating the level of knowledge about IMD in health sciences students, similar to our findings, the majority of students reported that they used the internet to increase their knowledge about IMD [ 11 ]. It is predicted that implementing a formal curriculum for IMDs through verified and reliable websites or online classes will result in highly effective learning.…”
Section: Discussionsupporting
confidence: 86%
“…When the knowledge levels of the individuals were evaluated, our findings were similar to the findings of recently published Saudi Arabia and Malaysia studies, concluding that both health and non-health sciences students lacked knowledge about the diagnosis and treatment of IMD [ 11 , 14 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations